2003
DOI: 10.1157/13043951
|View full text |Cite
|
Sign up to set email alerts
|

Estimación del riesgo coronario en España mediante la ecuación de Framingham calibrada

Abstract: Introduction and objectives. The Framingham coronary heart disease (CHD) functions overestimate the risk of CHD in countries with a low incidence. Consequently, these functions should be calibrated for the purpose of primary prevention. Calibrated Framingham function charts of overall CHD risk for the Spanish population are presented. Patients and methods. The Framingham functions were calibrated by substituting the prevalence of CHD risk factors and incidence found in Framingham with the same values for Spain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
45

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(81 citation statements)
references
References 24 publications
3
33
0
45
Order By: Relevance
“…To this end, several previous studies have examined multiple ethnic or racial groups in an effort to test the utility or validity of the FRS. Several investigators have demonstrated the overestimation of cardiovascular risk when FRS was directly applied to other ethnicities, such as in Asia including South Korea and several countries in Europe [17][18][19][20][21][22]. In a study based on a Korean population, the investigators reported that FRS overestimated CAD risk and CAD incidence was low [18].…”
Section: Rationale Behind the Koica Registrymentioning
confidence: 99%
“…To this end, several previous studies have examined multiple ethnic or racial groups in an effort to test the utility or validity of the FRS. Several investigators have demonstrated the overestimation of cardiovascular risk when FRS was directly applied to other ethnicities, such as in Asia including South Korea and several countries in Europe [17][18][19][20][21][22]. In a study based on a Korean population, the investigators reported that FRS overestimated CAD risk and CAD incidence was low [18].…”
Section: Rationale Behind the Koica Registrymentioning
confidence: 99%
“…The risk functions used in this study include the Framingham function 17 and the REGICOR adaptation to the risk factor prevalence and event characteristics of the population in Spain. 15 …”
Section: Risk Functionsmentioning
confidence: 99%
“…Obtaining such indicators requires knowing in anticipation both the prevalence of RF in the community and the associated relative risks, ideally coming from population-based prospective studies. From an individual perspective, however, charts of coronary risk are used to predict the chance of suffering a CV event within a certain period of time [8-10]. Those nowadays available in Spain, however, rely on risk estimates available for the USA (REGICOR) [8] or European (SCORE) [9] populations.…”
Section: Introductionmentioning
confidence: 99%
“…From an individual perspective, however, charts of coronary risk are used to predict the chance of suffering a CV event within a certain period of time [8-10]. Those nowadays available in Spain, however, rely on risk estimates available for the USA (REGICOR) [8] or European (SCORE) [9] populations. Both, REGICOR and SCORE are calibrations of the Framingham and SCORE risk functions, respectively, but only the first has been validated for use in Spain [11].…”
Section: Introductionmentioning
confidence: 99%